PREPARING WORKPLACE-READY STUDENTS WITH DIGITAL MARKETING SKILLS. Issue 2 (3rd April 2019) - Key, Thomas M.; Czaplewski, Andrew J.; Ferguson, Jeffery M.
Abstract : Digital marketing practice continues to grow along with the need for a qualified workforce. This paper presents a course design intended to teach students how to use relevant digital marketing tools and give them an end-to-end experience and managerial control over key resources. Students leave the course with real-world skills and items for their résumé to demonstrate workplace readiness. The project lays out how students create original content, perform keyword research, implement Google Ads and social media pay-per-click campaigns, analyze results, course correct, present a final report, and become Google Ads Certified. Innovation effectiveness is tested and reported.